A study of the readiness of post-pandemic computer-based four-tier diagnostic test (CBFTDT): A review of economic level, school grades, and device accessibility - Istiyono, Edi; Dwandaru, Wipsar Sunu Brams; Ayub, Made Rai Shanti; Saepuzaman, Duden; Zakwandi, Rizki; Rachman, Anisyah; Yusron, Eri; Santoso, Purwoko Haryadi (Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
Student readiness for using computer-based assessment was affected by economic level, school grade, and device accessibility. This study analyzed student readiness using a computer-based assessment, the four-tier diagnostic test (CBFTDT). The data in this study were students' responses to a questionnaire consisting of 16 statements about three aspects: mental access, skill access, and usage. The questionnaire consists of 16 statements with three aspects: items, media, and effectivity. The questionnaire was proved valid by experts and its estimated reliability score was 0.99. This study proved that the Student is still not ready to use the computer-based assessment, with an average readiness of 60%. In addition, there is no effect of economic level, school grade, and device accessibility on the readiness for using the computer-based assessment. Hence, the treatment of all stockholders is needed to prepare students to use the computer-based assessment.